2010
DOI: 10.1007/s00464-010-1286-5
|View full text |Cite
|
Sign up to set email alerts
|

Risk of recurrence after laparoscopy-assisted radical gastrectomy for gastric cancer performed by a single surgeon

Abstract: LAG and OG did not differ significantly in terms of recurrence, even when used in advanced gastric cancer cases. Multivariate analysis revealed that high TNM stage was significantly associated with recurrence. Thus, LAG appears to be a safe and feasible procedure that has the potential to be an alternative to open surgery, even for advanced gastric cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
19
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 30 publications
0
19
0
Order By: Relevance
“…Based on the paradigm of advanced colon cancer with evidence that laparoscopic colectomy in stage II/III has no negative effect on disease-free survival, the trend is to evaluate the safety and efficacy of laparoscopic gastrectomy in advanced stages. The study by Jeong et al [1] supports the safety of laparoscopic surgery for advanced gastric cancer. However, this study is limited by its retrospective nature and relatively small number of patients in each TNM stage.…”
mentioning
confidence: 81%
See 2 more Smart Citations
“…Based on the paradigm of advanced colon cancer with evidence that laparoscopic colectomy in stage II/III has no negative effect on disease-free survival, the trend is to evaluate the safety and efficacy of laparoscopic gastrectomy in advanced stages. The study by Jeong et al [1] supports the safety of laparoscopic surgery for advanced gastric cancer. However, this study is limited by its retrospective nature and relatively small number of patients in each TNM stage.…”
mentioning
confidence: 81%
“…To highlight this crucial question, Jeong et al [1] performed a retrospective study and reported the results in the March issue of Surgical Endoscopy. The authors evaluated the clinicopathologic, treatment, and survival follow-up data of 398 patients with gastric cancer who underwent an R0 resection.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…A small-scale RCT and several retrospective studies have demonstrated no significant differences in survival rate, recurrence rate and type of recurrence between LAG and COG (12,(24)(25)(26). Furthermore, a retrospective study by multivariate analysis found that depth of invasion and progression of lymph node metastasis were determinants of prognosis, indicating that survival was not an issue of approach, i.e.…”
Section: Evidence Regarding Long-term Survival Outcomesmentioning
confidence: 99%
“…Furthermore, a retrospective study by multivariate analysis found that depth of invasion and progression of lymph node metastasis were determinants of prognosis, indicating that survival was not an issue of approach, i.e. laparoscopy versus laparotomy (25). However, observation periods were <5 years in most studies, and prospective studies were conducted in a small scale, and therefore, it must be said that evidence that the long-term outcomes of laparoscopy are equivalent to those of laparotomy is still insufficient.…”
Section: Evidence Regarding Long-term Survival Outcomesmentioning
confidence: 99%